Strengthening Self Efficacy and Self Care Practices Among People Formerly Affected by Leprosy to Reduce Disability Risk - Bakhtiar, Rahmat; Duma, Krispinus; Rahayu, Hanis Kusumawati; Sawitri, Endang (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Disability progression among people formerly affected by leprosy can occur due to permanent nerve damage involving the hands, feet, and eyes. Consistent self care can prevent or reduce secondary injury and disability. This community service program aimed to increase self efficacy and knowledge related to self care practices. A refresher program comprising education and motivational support was delivered to 20 participants who had a history of leprosy and varying levels of disability. Self efficacy and self care activities were assessed before and after the program. At baseline, conditions that support self efficacy were limited. After the intervention, improvements were observed across multiple elements of self care, particularly reduced wound odor, improved hand condition with cleaner and softer skin, and increased use of protective footwear and gloves during work activities. Participants reported that prior successful experiences with self care and support from peers, other people formerly affected by leprosy, and family members helped strengthen self efficacy and supported more consistent self care. These findings suggest that refresher education combined with social support can reinforce self care behaviors, which may help participants maintain daily self care practices.